2006
DOI: 10.1002/ajh.20655
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating platelet–neutrophil, platelet–monocyte complexes, and platelet activation in patients with ulcerative colitis: A comparative study

Abstract: It is reported that the incidence of thromboembolism is increased in ulcerative colitis (UC), and hypercoagulability persists even when patients are in remission. We evaluated the association of inflammatory response parameters with UC activity, and activation parameters of the platelets, endothelium, and the coagulation system in UC. Eighteen UC patients and 19 healthy subjects were included in the study. The patients' clinical features were recorded down; whole blood counts and acute phase parameters were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…Despite circulating in both blood and biological fluids in healthy individuals, MPs have been implicated in a wide spectrum of diseases, including cardiovascular disease [2][3][4] , diabetes [5] , inflammatory states [6,7] , sepsis [8] , antiphospholipid antibody syndrome [9,10] , thrombotic thrombocytopenic purpura [11] and cancer [12] . Many of these conditions are characterized by a hypercoagulable state, which may lead to thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite circulating in both blood and biological fluids in healthy individuals, MPs have been implicated in a wide spectrum of diseases, including cardiovascular disease [2][3][4] , diabetes [5] , inflammatory states [6,7] , sepsis [8] , antiphospholipid antibody syndrome [9,10] , thrombotic thrombocytopenic purpura [11] and cancer [12] . Many of these conditions are characterized by a hypercoagulable state, which may lead to thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that there is an increase in the concentration of IL-6 in ulcerative colitis and its role is to initiate, potentiate and sustain the inflammatory process in the inflamed mucous membrane of the colon [8][9][10]. Cytokines and interactions between blood cells cause the activation of blood platelets [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…Palkovits et al [15] found increased PDMPs levels only in patients with quiescent IBD compared to controls, but no difference in PDMPs levels was reported when active and quiescent patient groups were compared. Pamuk et al [16] failed to show any increase in PDMPs levels in UC patients and they even reported increased PDMPs levels in healthy controls compared to inactive UC patients. Finally, Leonetti et al [17] displayed increased PDMPs only in active CD patients compared to healthy controls, while a UC population was absent.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies revealed overall elevated PDMPs levels in IBD compared to healthy controls (Table 3 summarizes data from available studies). [13][14][15][16][17] However, to the best of our knowledge, unanswered remains the question as to whether established IBD medication treatments pose any impact on PDMPs levels. Our work illustrates that (i) there is significant increase of studied PDMPs levels, including those bearing exposed phosphatidylserine in CD patients compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation